Teaching beyond expertise: a case study of out-of-field teachers by qualification in basic education - Durano, Jeanette Rose; Layasan, Marjorie L.; Maramara, Olcee C.; Neri, Precious Dianne N.; Orio, Psyber V.; Tan, Emerita M.; Mutya, Romel C. (Intelektual Pustaka Media Utama, 2026)
In a global context of increasing demands for diverse skill sets and innovative teaching, the phenomenon of out-of-field teachers (OFT) by qualification has gained attention. This study explored teachers’ experiences transitioning between elementary and high school teaching. A descriptive case study phenomenological approach was employed, involving 7 participants selected through purposive sampling. Colaizzi’s seven-step method was utilized to analyze the data. Results indicated that OFT faces challenges such as limited subject matter knowledge, staying current in evolving fields, and adapting to diverse student needs. To cope, they seek professional development, collaborate with colleagues, and understand different learning styles. Teaching outside their expertise makes educators adaptable, resilient facilitators committed to continuous professional development. Handling unfamiliar content enhances problem-solving skills and resourcefulness in discovering effective teaching strategies. The research highlights the transformative impact of transitioning between elementary and high school levels, resulting in versatile, creative, and passionate educators dedicated to continuous improvement in education.